SISTEM KEAMANAN BERBASIS IOT MENGGUNAKAN METODE R&D (STUDI KASUS : KAMPUS STMIK LOMBOK) - Hulaimi, Muhammad; Muhammad Fauzi Zulkarnaen; Wire Bagya (LPPM STMIK Lombok, 2025)
Abstract?The current condition of the STMIK Lombok campus security is still lacking in terms of security because there are no night watch guards or assistant track recorders other than other Closed Circuit Television (CCTV) that can help see events when there is a theft or suspicious activity of someone, such as an incident. In the past, there has been loss of motorbikes, damage to student motorbike keys in the parking lot east of the academic that occurred during lecture hours, and a few months ago there has been another loss of money in the academic room and also some tools as material for the final project in the UKM room, The incident occurred when STMIK LOMBOK's environmental conditions were quiet and on holiday in 2020 and yesterday lost a motorcycle parked in front of the southernmost gate during the morning hours of September 2022 yesterday, one of the motorcycles belonging to a new student that could not be monitored by CCTV because it was too far away. the distance. After the incident, a secret investigation was carried out by certain people and one of them was a security guard, but the results of the investigation did not find evidence and clear instructions. After seeing the events and problems that have occurred on the STMIK Lombok campus, the author proposes the title as follows